The anti-monument and the right to memory and truth: impressions from a case study - Cosme, Kaíque (Revista do Colóquio, 2021)
This article deals with an ongoing research project on the aesthetics of anti-monuments in Latin America, with the dictatorial processes implemented in the Southern Cone as its guiding theme. To this end, it is necessary to understand the political issues external to the continent that permeate it and drive military coups, as well as the changes that have occurred in the artistic scene since the second half of the 20th century. In this way, we can clearly understand the role played by the anti-monument and the changes it has undergone as a model of testimonial art.